The message of a number Psalms as interpreted in Syriac Psalm headings - Van Rooy, H. F. (Verbum et ecclesia, 1998)
Following the view of Theodore of Mopsuestia, the translator(s) of the Peshitta Psalter did not accept the historicity of the headings of the Psalms in the Hebrew Psalter. In some manuscripts the Peshitta Psalms do not have headings at all, while in other manuscripts headings are supplied. This paper makes a few remarks on the study of the headings of the Psalms in Syriac and discusses the headings of a number of Psalms in different Syriac traditions, with special attention to the headings in the Syriac manuscript 12t4. These headings can be regarded as a summary of the exegesis of the particular Psalm and they represent different schools of exegetes with widely different interpretations of most of the Psalms.